2007
DOI: 10.1038/sj.cr.7310138
|View full text |Cite
|
Sign up to set email alerts
|

Promoting human embryonic stem cell renewal or differentiation by modulating Wnt signal and culture conditions

Abstract: We previously showed that Wnt3a could stimulate human embryonic stem (hES) cell proliferation and affect cell fate determination. In the absence of feeder cell-derived factors, hES cells cultured under a feeder-free condition survived and proliferated poorly. Adding recombinant Wnt3a in the absence of feeder cell derived-factors stimulated hES cell proliferation but also differentiation. In the present study, we further extended our analysis to other Wnt ligands such as Wnt1 and Wnt5a. While Wnt1 displayed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
70
2
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 80 publications
(79 citation statements)
references
References 44 publications
6
70
2
1
Order By: Relevance
“…These data were later supported by other research groups (14,67,73,86,88,113). Several studies have independently described cardiac stem=progenitor cell isolation from various species, including murine, rat, feline, pig, dog, and human, that display stem= progenitor cell characteristics (5,18,60,73,88,117).…”
Section: Cardiac Stem=progenitor Cellssupporting
confidence: 51%
See 1 more Smart Citation
“…These data were later supported by other research groups (14,67,73,86,88,113). Several studies have independently described cardiac stem=progenitor cell isolation from various species, including murine, rat, feline, pig, dog, and human, that display stem= progenitor cell characteristics (5,18,60,73,88,117).…”
Section: Cardiac Stem=progenitor Cellssupporting
confidence: 51%
“…Various strategies have been successfully adopted to address these issues. Genetic selection of differentiated ES cells or their partial differentiation into cardiomyocytes or endothelial cells in vitro before engraftment has given encouraging results in experimental animal models (13,14,34,76). Further insight from the heart development studies and discovery of the signaling pathways involved in ES cell differentiation will facilitate isolation of the pure population of cardiomyocytes, thereby limiting the risk of teratoma formation.…”
Section: Haider Et Almentioning
confidence: 99%
“…sFRP-1 contains a domain homologous to the cysteine-rich domain of Fzd and will bind to WNT, inhibiting WNT's interaction with Fzd and blocking activation of the b-catenin pathway [60]. This pathway is known to have a key role in stem cell proliferation and maintenance of pluripotency through activation of NANOG and other factors such as OCT4 [61,[63][64][65][66][67][68][69], although increased WNT signaling has also been associated with hESC differentiation [70]. Thus, disruption of this pathway is a plausible mechanism for sFRP-1's inhibitory activity in our hESC growth assays.…”
Section: Discussionmentioning
confidence: 99%
“…The TW3R cell line was created by transducing TW2R with a lentiviral vector expressing puromycin resistance (Puro R ) gene. The retroviral and lentiviral vectors were previously described [18].…”
Section: Immortalization and Engineering Of Human Mscmentioning
confidence: 99%
“…This underlies the need to develop systems that can sufficiently support human iPSC clonal growth and have the potential to be compatible with clinical production under current Good Manufacturing Practice (cGMP) standards. We have previously demonstrated that human adult marrow stromal cells [also called mesenchymal stem cells (MSCs)] could efficiently support undifferentiated growth of hESCs [16] and that selfrenewal of hESCs can be promoted by modulating the Wnt signaling pathway [17,18]. It has also been reported that MSCs facilitated the derivation of hESCs from cryopreserved poor-quality embryos [19].…”
mentioning
confidence: 99%